Yield and production components in maize hybrids in the Comarca Lagunera. - Borroel García, Victoria Jared; Salas Pérez, Lilia; Ramírez Aragón, Mercedes Georgina; López Martínez, José Dimas; Luna Anguiano, Jesús (REVISTA TERRA LATINOAMERICANA, 2018)
The shortage of corn grain for human consumption makes it necessary to improve its production efficiency by making an adequate selection of hybrids with characteristics that are adaptable to a given region. The objective of this research was to evaluate five maize hybrids for yield and production components in the Comarca Lagunera. The hybrids evaluated were SB302 (control), RX715, Cayman, Bear and Ocelot, which were established in the field under a randomized complete block design. The hybrids Cayman, RX715, Bear and SB302 obtained the highest grain yields, 14.52 to 15.84 Mg ha-1. Production components had a positive correlation with length and diameter of ear (r = 0.74), length of ear and grains per row (r = 0.83), length of ear and total grains per ear (r = 0.81). Also, ear diameter correlated with grains per row (r = 0.62), number of rows with total grains per ear (r = 0.51), and grains per row with total grains per ear (r = 0.86). Yield positively correlated with diameter (r = 0.90) and ear length (r = 0.77). The Cayman hybrid was the hybrid that obtained a yield (15.84 Mg ha-1) superior to the national average in corn grain. Therefore, to potentiate maize production in the region of the Comarca Lagunera, this hybrid is recommended.